Determination of adenosine phosphates in whole blood by capillary zone electrophoresis - Kamarýt, J; Muchová, M; Stejskal, J (European journal of clinical chemistry and clinical biochemistry, 1996)
The pool of chemical energy in an organism represented by high-energy compounds can be assessed by means of adenosine triphosphate (ATP) determination in whole blood and tissues. The elegant manner for the determination of adenosine phosphates (ATP, ADP, AMP) in a single assay is offered by the technique of capillary zone electrophoresis. For this purpose, the BioFocus 3000 Capillary Electrophoresis System (BIO-RAD Laboratories, Inc., Hercules, CA, USA) was used. For the construction of calibration curves, pure preparations of ATP, ADP and AMP were analyzed. The method was used for adenosine phosphates determination in the umbilical blood samples from physiological and immature newborns. Capillary zone electrophoresis enables a specific and simultaneous determination of adenosine phosphates and, thus, monitoring of unusual metabolic situations.
Keywords: Humans; Adenine Nucleotides; Adenosine Triphosphate; adenosindifosfát; adenosinmonofosfát; adeninnukleotidy; Adenosine Diphosphate; Electrophoresis, Capillary; elektroforéza kapilární; lidé; Adenosine Monophosphate; adenosintrifosfát